MINDP-MAPPING AS A TOOL OF ORGANIZING SELF-DEPENDENT COGNITIVE ACTIVITY OF CADETS ON PHYSICS - Solodovnik А.О. (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the possibility of using mind-mapping in organizing of self-dependent work of cadets on physics and suggested examples of tasks for their implementation.